Semisynthetic Derivative of Artemisia annua-Loaded Transdermal Bioadhesive for the Treatment of Uncomplicated Malaria Caused by Plasmodium falciparum in Children - Volpe Zanutto, Fabiana; McAlister, Emma; Marucci Pereira Tangerina, Marcelo; Fonseca-Santos, Bruno [UNESP]; Costa Salles, Taís Helena; Oliveira Souza, Ilza Maria; Brisibe, Andi; Vilegas, Wagner [UNESP]; Chorilli, Marlus [UNESP]; Akira d’Ávila, Marcos; Donnelly, Ryan F.; Foglio, Mary Ann (Elsevier, 2019)
According to the most recent World Health Organization statistics, malaria infected approximately 219 million people in 2017, with an estimate of 435,000 deaths (World Health Organization, 2018). Communities isolated from cities are the most deprived of access to the necessary hospital facilities. Herein we report the development of a transdermal bioadhesive containing artemether (ART), an alternative, potentially lifesaving, treatment regimen for malaria in low-resource settings. Bioadhesives were prepared from an aqueous blend of hydroxyethylcellulose (4.5% w/w), ART, propoxylated-ethoxylated-cetyl-alcohol, polysorbate 80, propyleneglycol, glycerine, mineral oil, and oleic acid. In this study, the average pore size of bioadhesive 5.5b was 52.6 ± 15.31 μm. Differential scanning calorimetry and thermogravimetric analyses confirm the thermal stability of ART bioadhesives at room temperature. Tensile tests indicated good mechanical properties for bioadhesive 5.5b, when compared to 5.5a, where 5.5b showed elastic modulus 0.19 MPa, elongation at break 204%, tensile stress 0.31 MPa, tensile strength at break 0.23 MPa. Bioadhesion assays suggested that formulations containing surfactants had higher detachment forces. Permeation studies demonstrated that the best outcome was achieved with a bioadhesive containing 25 mg ART (5.5b) that after 24 h released 6971 ± 125 μg, which represents approximately 28% of drug permeation. Data reported presents a promising candidate for a new antimalarial transdermal formulation.
Keywords: artemether; bioadhesives; hydroxyethylcellulose; malaria; Plasmodium falciparum